2021
DOI: 10.3389/fclim.2021.714273
|View full text |Cite|
|
Sign up to set email alerts
|

Limitations of Remote Sensing in Assessing Vegetation Damage Due to the 2019–2021 Desert Locust Upsurge

Abstract: The 2019–2020 Desert Locust (DL) upsurge in East Africa threatened food security for millions in the region. This highlighted the need to track and quantify the damaging impacts of the swarming insects on cropland and rangelands. Satellite Earth observations (EO) data have the potential to contribute to DL damage assessments that can inform control measures, aid distribution and recovery efforts. EO can complement traditional ground based surveys (which are currently further limited due to COVID-19), by rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To address this objective, field data with specific information on ground detected vegetation damage and timely coupled satellite data at higher spatial, temporal, and spectral resolution are required. Previous investigations utilizing MODIS data showed that optical moderate-resolution sensors might be insufficient to detect vegetation damage related to locust infestation [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…To address this objective, field data with specific information on ground detected vegetation damage and timely coupled satellite data at higher spatial, temporal, and spectral resolution are required. Previous investigations utilizing MODIS data showed that optical moderate-resolution sensors might be insufficient to detect vegetation damage related to locust infestation [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data analytics methods, such as regression and machine learning, have been applied to predict breeding areas of DL (Piou et al, 2013;Gómez et al, 2018;Kimathi et al, 2020;Ellenburg et al, 2021;Klein et al, 2022), potential habitat areas of DL Meynard et al (2017); Guan et al (2021); Saha et al (2021); Youngblood et al (2022), presence of DL (Tratalos et al, 2010;Piou et al, 2019;Samil et al, 2020;Tabar et al, 2021;Gómez et al, 2021a;Shao et al, 2021;Yusuf et al, 2021;Sun et al, 2022;Rhodes and Sagan, 2022;Cornejo-Bueno et al, 2022) and the incidence of locust outbreaks ((Lawton et al, 2022)). They have also been applied to detect DL impact on vegetation senescence (Adams et al, 2021), and cropland damage (Alemu and Neigh, 2022). Major challenges remain in spatiotemporal forecasting of DL, in particular to predict the long-range movements of swarms.…”
Section: Introductionmentioning
confidence: 99%